2007
DOI: 10.1158/1541-7786.mcr-06-0071
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of X-Linked Genes RbAp46, Rsk4, and Cldn2 in Breast Cancer

Abstract: The consequence of activation status or gain/loss of an X-chromosome in terms of the expression of tumor suppressor genes or oncogenes in breast cancer has not been clearly addressed. In this study, we investigated the activation status of the X-chromosomes in a panel of human breast cancer cell lines, human breast carcinoma, and adjacent mammary tissues and a panel of murine mammary epithelial sublines ranging from low to high invasive potentials. Results show that most human breast cancer cell lines were hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 27 publications
2
59
2
Order By: Relevance
“…RSK4 has previously been characterized as essential for p53-dependent proliferation arrest as well as stress-and oncogene-induced senescence (28,58,59). Interestingly, the RSK4 isoform exhibits constitutively high activity, is upregulated in MMTV-Myc mouse breast tumors, is aberrantly expressed in breast cancer, and has been implicated in sunitinib resistance (58,(60)(61)(62)(63). Here, we demonstrate that RSK3 and RSK4 can also mediate resistance to PI3K inhibitors in breast cancer cells both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 62%
“…RSK4 has previously been characterized as essential for p53-dependent proliferation arrest as well as stress-and oncogene-induced senescence (28,58,59). Interestingly, the RSK4 isoform exhibits constitutively high activity, is upregulated in MMTV-Myc mouse breast tumors, is aberrantly expressed in breast cancer, and has been implicated in sunitinib resistance (58,(60)(61)(62)(63). Here, we demonstrate that RSK3 and RSK4 can also mediate resistance to PI3K inhibitors in breast cancer cells both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 62%
“…The above results suggest that RSK4 can inhibit cell proliferation. Thakur et al (19) revealed higher expression of RSK4 was found in normal mammary ductals, and low expression or no expression of RSK4 in benign breast lesions (papilloma). RSK4 is likely to have a role in the development or progression of human breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, aberrant RSK activation contributes to multiple malignant conditions, including various breast and ovarian cancers and myeloma (47)(48)(49)(50). Additionally, inactivating mutations in the RSK2-encoding gene are responsible for Coffin-Lowry syndrome, which is characterized by severe mental retardation and progressive skeletal deformations (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%